Homozygous IL37 mutation associated with infantile inflammatory bowel disease - ÖZEN, AHMET OĞUZHAN; ERTEM ŞAHİNOĞLU, DENİZ; AYDINER, ELİF; BARIŞ, SAFA (NATL ACAD SCIENCES, 2021)
Interleukin (IL)-37, an antiinflammatory IL-1 family cytokine, is a key suppressor of innate immunity. IL-37 signaling requires the heterodimeric IL-18R1 and IL-1R8 receptor, which is abundantly expressed in the gastrointestinal tract. Here we report a 4-mo-old male from a consanguineous family with a homozygous loss-of-function IL37 mutation. The patient presented with persistent diarrhea and was found to have infantile inflammatory bowel disease (I-IBD). Patient cells showed increased intracellular IL-37 expression and increased proinflammatory cytokine production. In cell lines, mutant IL-37 was not stably expressed or properly secreted and was thus unable to functionally suppress proinflammatory cytokine expression. Furthermore, induced pluripotent stem cell-derived macrophages from the patient revealed an activated macrophage phenotype, which is more prone to lipopolysaccharide and IL-1 beta stimulation, resulting in hyperinflammatory tumor necrosis factor production. Insights from this patient will not only shed light on monogenic contributions of I-IBD but may also reveal the significance of the IL-18 and IL-37 axis in colonic homeostasis.
Keywords: immunodeficiency; inflammatory bowel disease; IBD; IL37; VEO-IBD; IL-37; EXPRESSION; SIGIRR